2018
DOI: 10.24875/nefro.18000048
|View full text |Cite
|
Sign up to set email alerts
|

A remote management program in automated peritoneal dialysis patients in Colombia

Abstract: Background: Remote monitoring technology that is specifically designed to be integrated into automated peritoneal dialysis (APD) systems gives both patients and their clinical team a powerful tool that can enhance communication, potentially improve adherence to the treatment, optimize fluid balance, and address potential complications of therapy in near real time. Objective: The objective of this study was to describe the implementation and early stages of an APD remote monitoring program as well as some early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 14 publications
0
60
1
Order By: Relevance
“…It has been shown that dialysis prescription adherence became more than 90% with the use of RM-APD. 31 We observed an improvement in patients' office blood pressure measurements, with approximately 30% less anti-hypertensive drugs in patients with performing RM-APD at the end of 1 year observation period.…”
Section: Discussionmentioning
confidence: 57%
“…It has been shown that dialysis prescription adherence became more than 90% with the use of RM-APD. 31 We observed an improvement in patients' office blood pressure measurements, with approximately 30% less anti-hypertensive drugs in patients with performing RM-APD at the end of 1 year observation period.…”
Section: Discussionmentioning
confidence: 57%
“…Figure 2 was depicted to demonstrate how patients' treatment adherence has changed after switching to RM-APD. According to Figure 2, alarms received from the device decreased within months, and treatment adherence of patients increased (from 4 [3][4][5][6][7][8] to 2 [0-3], p = 0.001). Also, patient median body weight decreased from 62.7 to 61 kg within 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…When a problem is detected, the physician and/ or PD nurse could interfere actively by either arranging the remote treatment (change the prescription using remote connection) or contacting the patient. It has been shown that dialysis prescription adherence became more than 90% with the use of RM-APD [5]. A study that is focused on outcomes of using RM-APD and published in 2019 showed that the use of RM-APD is associated with reduced hospital visits, nonsignificant but increased technical survival and reduced health costs during 1 year of follow-up [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall non-adherence rates to peritoneal dialysis prescription were 2.6% to 85% in the literature, and non-adherence to APD prescription was reported to be 5% to 20% 23,24 . It has been shown that dialysis prescription adherence became more than 90% with the use of RM-APD 7,25 . This platform enables patient treatment data, including peritoneal volume, alerts during treatment, drainage problems, interruption of therapy, loss of dwell time, loss of therapy time to receive, and transmission through to the PD center 7,9 .…”
Section: Discussionmentioning
confidence: 99%